PENGARUH PROFITABILITAS, SOLVABILITAS, LIKUIDITAS, DAN NILAI PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN YANG TERINDEKS LQ45 PADA BURSA EFEK INDONESIA (BEI) - Lantasari, Desak Putu Satria; Widnyana, I Wayan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
This study aims to determine and analyze the influence of profitability, solvency, liquidity ratios and corporate value to stock return, either simultaneously or partially. Profitability uses the proxy of return on assets (ROA), liquidity uses the proxy of debt to equity (DER), solvency using current ratio(CR), and firm value usingprice to book value (PBV). This study was conducted at companies indexed LQ45 at Indonesia Stock Exchange (BEI). Determination of samples with porposive sampling obtained 13 companies for three years, so the number of observations to 39 companies. The model feasibility test uses the classical assumption test. Data analysis techniques use multiple linear regression analysis, multiple correlation analysis and determination analysis. The significance test using t test and F test with theSPSS program V.23. The result of analysis is obtained as follows: (a) return on asset (ROA) has no effect on stock return, (b) debt to equity ratio (DER) has no effect on return saham,(c) current ratio (CR) has no significant effect on stock return, (d) price to book value (PBV) has a significant positive effect on stock return.